First report of melon and cucumber plants as natural hosts of cowpea mild mottle virus - B. A. Silva; C. M. Kauffmann; S. B. S. Cardenas; P. S. Queiroz; A. M. V. Batista; H. B. S. Mota; A. K. Inoue-Nagata; D. M. S. Freitas; Tatsuya Nagata (Journal of Plant Pathology, 2026)

P19-40 Risk assessment of AFB1 due to CYP3A4-mediated biotransformation with a highly sensitive human intestinal model - L. Bai; K. Tachibana; M. Murata; T. Inoue; H. Mizuguchi; S. Maeda; K. Ikemura; M. Okuda; T. Kusakabe; M. Kondoh (Toxicology Letters, 2024)

Hybridization and reticulate evolution in Diphasiastrum (flat-branched clubmosses, Lycopodiaceae) – New data from the island of Taiwan and Vietnam - M. Schnittler; M. Inoue; O.N. Shchepin; J. Fuchs; H. Chang; P. Lamkowski; R. Knapp; K. Horn; H.W. Bennert; M. Bog (Molecular Phylogenetics and Evolution, 2024)

Preliminary analysis focusing on in-vessel thermal hydraulics in loss-of-heat removal systems in a sodium-cooled fast reactor - H. Sonoda; S. Fujita; M. Inoue; T. Okawa (Annals of Nuclear Energy, 2023)

Distribution of natural radionuclides in NORM samples from North Abu Rusheid area, Egypt - S. Sakr; K. Inoue; A. Mohamed; A.A. Ahmed; M.G. ElFeky; G.M. Saleh; M.S. Kamar; H. Arae; T. Aono; S.K. Sahoo (Journal of Environmental Radioactivity, 2023)

Two Hidden mtDNA-Clades of Crown-of-Thorns Starfish in the Pacific Ocean - Nina Yasuda; Jun Inoue; Michael R. Hall; Manoj R. Nair; Mehdi Adjeroud; Miguel D. Fortes; Mutsumi Nishida; Nat Tuivavalagi; Rachel Ravago-Gotanco; Zac H. Forsman; Taha Soliman; Ryo Koyanagi; et al. (Frontiers in Marine Science, 2022)
Recurring outbreaks of crown-of-thorns starfish (COTS) severely damage healthy corals, especially in the Western Pacific Ocean. To obtain a better understanding of population genetics of COTS and historical colonization across the Pacific Ocean, complete mitochondrial genomes were sequenced from 243 individuals collected in 11 reef regions. Our results indicate that Pacific COTS ( Acanthaster cf. solaris ) comprise two major clades, an East-Central Pacific (ECP) clade and a Pan-Pacific (PP) clade, separation of which was supported by high bootstrap value. The ECP clade consists of COTS from French Polynesia, Fiji, Vanuatu and the Great Barrier Reef (GBR). The Hawaii population is unique within this clade, while California COTS are included in EPC clade. On the other hand, the PP clade comprises multiple lineages that contain COTS from Vietnam, the Philippines, Japan, Papua New Guinea, Micronesia, the Marshall Islands, GBR, Vanuatu, Fiji and French Polynesia. For example, a lineage of the PP clade, which has the largest geographic distribution, includes COTS from all of these locations. These results suggest two alternative histories of current geographic distributions of COTS in the Pacific Ocean, an ECP clade ancestry or Western Pacific clade ancestry. Although further questions remain to be explored, this discovery provides an evolutionary context for the interpretation of COTS population structure which will aid future coral reef research in the Pacific Ocean, and ultimately improve reef management of COTS.

Tolerance and acclimation of photosynthesis of nine urban tree species to warmer growing conditions - Chinatsu Hara; Sumihiro Inoue; H. Roaki Ishii; Momoko Okabe; Masaya Nakagaki; Hajime Kobayashi (Trees, 2021)

New Insights Into Dietary Toxin Metabolism: Diversity in the Ability of the Natricine Snake Rhabdophis tigrinus to Convert Toad-Derived Bufadienolides - Takato Inoue; Ryu Nakata; Alan H. Savitzky; Naoko Yoshinaga; Akira Mori; Naoki Mori (Journal of Chemical Ecology, 2021)

Expression profile of seven polyamine oxidase genes in rice (Oryza sativa) in response to abiotic stresses, phytohormones and polyamines - G. H. M. Sagor; Masataka Inoue; Tomonobu Kusano; Thomas Berberich (Physiology and Molecular Biology of Plants, 2021)

Enhanced vertical turbulent nitrate flux in the intermediate layer of the Kuroshio in the Tokara Strait - T. Tanaka; D. Hasegawa; I. Yasuda; D. Yanagimoto; S. Fujio; H. Nakamura; R. Inoue; J. Nishioka (Journal of Oceanography, 2021)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Variation in Bufadienolide Composition of Parotoid Gland Secretion From Three Taxa of Japanese Toads - Takato Inoue; Ryu Nakata; Alan H. Savitzky; Naoko Yoshinaga; Akira Mori; Naoki Mori (Journal of Chemical Ecology, 2020)

Integrative taxonomy reveals a new species of freshwater mussel, Potamilus streckersoni sp. nov. (Bivalvia: Unionidae): implications for conservation and management - Chase H. Smith; Nathan A. Johnson; Kentaro Inoue; Robert D. Doyle; Charles R. Randklev (Systematics and Biodiversity, 2019)

Spatial variation in low-level 134Cs in the coastal sediments off central Honshu in the Sea of Japan: implications for delivery, migration, and redistribution patterns - Mutsuo Inoue; H. Uemura; H. Kofuji; K. Fujimoto; H. Takata; Y. Shirotani; N. Kudo; S. Nagao (Journal of Oceanography, 2017)

Factors affecting water availability for high Arctic lichens - T. Inoue; S. Kudoh; M. Uchida; Y. Tanabe; M. Inoue; H. Kanda (Polar Biology, 2017)

Morphological features of an endangered Japanese strain of Cyprinus carpio : reconstruction based on seven SNP markers - K. Atsumi; H. Y. Song; H. Senou; K. Inoue; K. Mabuchi (Journal of Fish Biology, 2017)
Morphological analyses of 183 specimens of Japanese common carp Cyprinus carpio (171 from Lake Biwa and 12 from nursery ponds) using genetic hybrid indices demonstrated that the typical native Japanese strain of C. carpio has a more elongate body, more branched dorsal‐fin rays, fewer and shorter gill rakers, more developed pneumatic bulb, more coiled pneumatic duct, longer posterior swimbladder and shorter intestine than the typical introduced C. carpio . These results provide a basis for a better understanding of the ecological characteristics and taxonomic status of the endangered Japanese strain of C. carpio .

Simultaneous spawning by female stream goby Rhinogobius sp. and the association with brood cannibalism by nesting males - S. Ito; H. Iwao; J. Sakata; M. Inoue; K. Omori; Y. Yanagisawa (Journal of Fish Biology, 2016)
A laboratory experiment was conducted by varying the undersurface area of nesting substratum and the number of females in an experimental tank to elucidate the determinants of the mating pattern in the stream goby, Rhinogobius sp. cross‐band type. Males with larger nests tended to attract two or more females to their nest in a tank. Moreover, males spawned simultaneously with multiple females and entire brood cannibalism by males was rarely observed under a female‐biased sex ratio. When males spawned with a single female with low fecundity, however, entire brood cannibalism occurred at a high frequency, suggesting that a male guarding a nest with fewer eggs consumes the brood. Therefore, spawning behaviour of females that leads to a large egg mass would decrease the risk of entire brood cannibalism. In this species, simultaneous spawning by multiple females in a nest serves as a female counter‐measure against entire brood cannibalism. These results suggest that a conflict of interest between the sexes through brood cannibalism is a major determinant of simultaneous spawning.

A correlation of reactive oxygen species accumulation by depletion of superoxide dismutases with age-dependent impairment in the nervous system and muscles of Drosophila adults - Saori Oka; Jun Hirai; Takashi Yasukawa; Yasuyuki Nakahara; Yoshihiro H. Inoue (Biogerontology, 2015)

Screening for potentially hazardous PRTR chemicals in the Lake Biwa-Yodo River basin of Japan using a one-box multimedia model - B. H. A. K. T. Ariyadasa; Akira Kondo; Yoshio Inoue (Environmental Science and Pollution Research, 2015)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Methylmercury Monitoring Study in Karakuwacho Peninsula Area in Japan - Junxia Yan; Kayoko Inoue; Akihiro Asakawa; Kouji H. Harada; Takao Watanabe; Noriyuki Hachiya; Akio Koizumi (Bulletin of Environmental Contamination and Toxicology, 2014)

Analyzing flood risk and related impacts to urban communities in central Vietnam - Bam H. N. Razafindrabe; Ryohei Kada; Makoto Arima; Shoji Inoue (Mitigation and Adaptation Strategies for Global Change, 2014)

Expression of the bacterial heavy metal transporter MerC fused with a plant SNARE, SYP121, in Arabidopsis thaliana increases cadmium accumulation and tolerance - Masako Kiyono; Yumiko Oka; Yuka Sone; Michitaka Tanaka; Ryosuke Nakamura; Masa H. Sato; Hidemitsu Pan-Hou; Kou Sakabe; Ken-ichiro Inoue (Planta, 2012)

Roles of histone H3K9 methyltransferases during Drosophila spermatogenesis - Yuta Ushijima; Yoshihiro H. Inoue; Takahiro Konishi; Daishi Kitazawa; Hideki Yoshida; Kouhei Shimaji; Hiroshi Kimura; Masamitsu Yamaguchi (Chromosome Research, 2012)

Holocene uplifted coral reefs in Lanyu and Lutao Islands to the southeast of Taiwan - S. Inoue; H. Kayanne; N. Matta; W. S. Chen; Y. Ikeda (Coral Reefs, 2011)

Enhanced Inhibitory Effects of TBT Chloride on the Development of F1 Rats - H. Asakawa; M. Tsunoda; T. Kaido; M. Hosokawa; C. Sugaya; Y. Inoue; Y. Kudo; T. Satoh; H. Katagiri; H. Akita; M. Saji; M. Wakasa; et al. (Archives of Environmental Contamination and Toxicology, 2010)

The role of forest stand density in controlling soil erosion: implications to sediment-related disasters in Japan - Bam H. N. Razafindrabe; Bin He; Shoji Inoue; Tsugio Ezaki; Rajib Shaw (Environmental Monitoring and Assessment, 2010)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Reflectance characteristics of major land surfaces in slash‐and‐burn ecosystems in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2008)

Temporal variations in ozone concentrations derived from Principal Component Analysis - S. Yonemura; S. Kawashima; H. Matsueda; Y. Sawa; S. Inoue; H. Tanimoto (Theoretical and Applied Climatology, 2008)

Survey of Airborne Polyfluorinated Telomers in Keihan Area, Japan - Sayoko Oono; Eriko Matsubara; Kouji H. Harada; Sokichi Takagi; Sachiko Hamada; Akihiro Asakawa; Kayoko Inoue; Isao Watanabe; Akio Koizumi (Bulletin of Environmental Contamination and Toxicology, 2008)

Traceability of slash‐and‐burn land‐use history using optical satellite sensor imagery: a basis for chronosequential assessment of ecosystem carbon stock in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Fluctuating serotonergic function in premenstrual dysphoric disorder and premenstrual syndrome: findings from neuroendocrine challenge tests - Y. Inoue; T. Terao; N. Iwata; K. Okamoto; H. Kojima; T. Okamoto; R. Yoshimura; J. Nakamura (Psychopharmacology, 2006)

Development of Stable Isotope Dilution Quantification Liquid Chromatography–Mass Spectrometry Method for Estimation of Exposure Levels of Bisphenol A, 4-tert-Octylphenol, 4-Nonylphenol, Tetrabromobisphenol A, and Pentachlorophenol in Indoor Air - K. Inoue; S. Yoshida; S. Nakayama; R. Ito; N. Okanouchi; H. Nakazawa (Archives of Environmental Contamination and Toxicology, 2006)

The Monitoring of Insects to Maintain Biodiversity in Ogawa Fores Reserve - S. Makino; H. Goto; T. Inoue; M. Sueyoshi; K. Okabe; M. Hasegawa; K. Hamaguchi; H. Ctanaka; I. Okochi (Environmental Monitoring and Assessment, 2006)

Expression of foreign type I ribulose-1,5-bisphosphate carboxylase/ oxygenase (EC 4.1.1.39) stimulates photosynthesis in cyanobacterium Synechococcus PCC7942 cells - T. Iwaki; K. Haranoh; N. Inoue; K. Kojima; R. Satoh; T. Nishino; S. Wada; H. Ihara; S. Tsuyama; H. Kobayashi; A. Wadano (Photosynthesis Research, 2006)

Binding of tetrakis(pyrazoliumyl)porphyrin and its copper(II) and zinc(II) complexes to poly(dG-dC)2 and poly(dA-dT)2 - Daryono H. Tjahjono; Rahmana E. Kartasasmita; As’ari Nawawi; Shunsuke Mima; Takehiro Akutsu; Naoki Yoshioka; Hidenari Inoue (JBIC Journal of Biological Inorganic Chemistry, 2006)

High incidence of elevated antibody titers to Epstein-Barr virus in patients with uveitis - C. Touge; H. Agawa; T. Sairenji; Y. Inoue (Archives of Virology, 2006)

Assessment of room temperature influence on finger blood flow response induced by short-term grasping of vibrating handle - M. H. Mahbub; M. Inoue; K. Yokoyama; M. S. Laskar; H. Ohnari; K. Suizu; J. Inagaki; Y. Takahashi; N. Harada (International Archives of Occupational and Environmental Health, 2006)

High prevalence of hepatitis B, C and delta virus infections among blood donors in Mongolia - B. Tsatsralt-Od; M. Takahashi; T. Nishizawa; J. Inoue; D. Ulaankhuu; H. Okamoto (Archives of Virology, 2005)

Effect of room temperature on percentage finger systolic blood pressure response to finger cooling - M. S. Laskar; K. Ohmura; M. Inoue; K. Yokoyama; J. Inagaki; Y. Takahashi; M. H. Mahbub; H. Ohnari; N. Harada (European Journal of Applied Physiology, 2005)

Roles of Volume-sensitive Cl− Channel in Cisplatin-induced Apoptosis in Human Epidermoid Cancer Cells - T. Ise; T. Shimizu; E.L. Lee; H. Inoue; K. Kohno; Y. Okada (The Journal of Membrane Biology, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Augmented cytoplasmic Smad4 induces acceleration of TGF-?1 signaling in renal tubulointerstitial cells of hereditary nephrotic ICGN mice with chronic renal fibrosis; possible role for myofibroblastic differentiation - Y. Goto; N. Manabe; K. Uchio-Yamada; M. Yamaguchi-Yamada; N. Inoue; Y. Yamamoto; A. Ogura; N. Nagano; H. Miyamoto (Cell and Tissue Research, 2004)

The effects of histamine on the lipopolysaccharide-induced metallothionein-I mRNA expression in the mouse spleen - T. Inoue; M. Nakano; N. Oda; T. Yoneyama; Y. Okano; K. Onodera; H. Furuta; C. A. Sogawa; N. Sogawa (Inflammation Research, 2003)

Nucleotide sequences of the coat protein gene of potyviruses infecting Ornithogalum thyrsoides - S. Fuji; M. Inoue; H. Yamamoto; H. Furuya; H. Naito; T. Matsumoto (Archives of Virology, 2003)

In situ X-ray observations of phase transitions in MgAl 2 O 4 spinel to 40 GPa using multianvil apparatus with sintered diamond anvils - T. Irifune; H. Naka; T. Sanehira; T. Inoue; K. Funakoshi (Physics and Chemistry of Minerals, 2002)

The upr-1 gene encodes a catalytic subunit of the DNA polymerase ζ which is involved in damage-induced mutagenesis in Neurospora crassa - W. Sakai; C. Ishii; H. Inoue (Molecular Genetics and Genomics, 2002)

Complete nucleotide sequence of the genomic RNA of Aconitum latent virus (genus Carlavirus) isolated from Delphinium sp. - S. Fuji; H. Yamamoto; M. Inoue; K. Yamashita; Y. Fukui; H. Furuya; H. Naito (Archives of Virology, 2002)

Evaluation of formation potential of trihalomethanes and mutagens due to chlorination of river water along the Kizu River in the Yodo River system in Japan - S. Sanukida; T. Nobukawa; M. Ichihara; H. Shima; K. Inoue; S. Nakachi (Limnology, 2001)

Ecological Evaluation of Gadolinium Toxicity Compared with Other Heavy Metals Using an Aquatic Microcosm - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2001)

Simple Aquatic Microcosm for Ecotoxicity Screening at the Community Level - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2000)

A Neurospora Double-Strand-Break repair gene, mus-11, encodes a RAD52 homologue and is inducible by mutagens - Y. Sakuraba; A. L. Schroeder; C. Ishii; H. Inoue (Molecular Genetics and Genomics, 2000)

Subsite-specific risk factors for hypopharyngeal and esophageal cancer (Japan) - T. Takezaki; M. Shinoda; S. Hatooka; Y. Hasegawa; S. Nakamura; K. Hirose; M. Inoue; N. Hamajima; T. Kuroishi; H. Matsuura; K. Tajima (Cancer Causes & Control, 2000)

Physiological significance of hyperpolarization-activated inward currents (I h) in smooth muscle cells from the circular layers of pregnant rat myometrium - K. Okabe; Y. Inoue; T. Kawarabayashi; H. Kajiya; F. Okamoto; H. Soeda (Pflügers Archiv - European Journal of Physiology, 1999)

Physiological significance of hyperpolarization-activated inward currents ( I h ) in smooth muscle cells from the circular layers of pregnant rat myometrium - K. Okabe; Y. Inoue; T. Kawarabayashi; H. Kajiya; F. Okamoto; H. Soeda (Pflügers Archiv - European Journal of Physiology, 1999)

Biodiversity in deep-sea sites located near the south part of Japan - H. Takami; Kuniko Kobata; Takahiko Nagahama; Hideki Kobayashi; Akira Inoue; Koki Horikoshi (Extremophiles, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

An improved physical and genetic map of the genome of alkaliphilic Bacillus sp. C-125 - H. Takami; Kaoru Nakasone; Chie Hirama; Yoshihiro Takaki; Noriaki Masui; Fumie Fuji; Yuka Nakamura; Akira Inoue (Extremophiles, 1999)

Sequencing of three lambda clones from the genome of alkaliphilic Bacillus sp. strain C-125 - H. Takami; Kaoru Nakasone; Naotake Ogasawara; Chie Hirama; Yuka Nakamura; Noriaki Masui; Fumie Fuji; Yoshihiro Takaki; Akira Inoue; Koki Horikoshi (Extremophiles, 1999)

Selective complement C1s deficiency caused by homozygous four-base deletion in the C1s gene - Naokazu Inoue; Toshiyuki Saito; Riako Masuda; Yoshio Suzuki; Michiko Ohtomi; H. Sakiyama (Human Genetics, 1998)

Characterization of α-maltotetraohydrolase produced by Pseudomonas sp. MS300 isolated from the deepest site of the Mariana Trench - H. Kobayashi; Yoshihiro Takaki; Kuniko Kobata; Hideto Takami; Akira Inoue (Extremophiles, 1998)

Effects of various factors including the CYP2D6 genotype and coadministration of flunitrazepam on the steady-state plasma concentrations of bromperidol and its reduced metabolite - A. Suzuki; K. Otani; K. Mihara; N. Yasui; T. Kondo; N. Tokinaga; H. Furukori; S. Kaneko; Y. Inoue; K. Hayashi (Psychopharmacology, 1998)

The Urinary Excretion of Arsenic Metabolites After a Single Oral Administration of Dimethylarsinic Acid to Rats - K. Yoshida; H. Chen; Y. Inoue; H. Wanibuchi; S. Fukushima; K. Kuroda; G. Endo (Archives of Environmental Contamination and Toxicology, 1997)

Pyruvate alleviates toxic effects of ethanol on cells in culture - K. Fukaya; M. Miyazaki; H. Pu; B. Katayama; Y. Inoue; R. Ohashi; C. Nakamura; M. Namba (Archives of Toxicology, 1997)

Interaction between carbamazepine and bromperidol - K. Otani; M. Ishida; N. Yasui; T. Kondo; K. Mihara; A. Suzuki; H. Furukori; S. Kaneko; Y. Inoue (European Journal of Clinical Pharmacology, 1997)

Full-length genomic sequence of a hepatitis C virus genotype 2c isolate (BEBE1) and the 2c-specific PCR primers - H. Nakao; H. Okamoto; H. Tokita; T. Inoue; H. Iizuka; G. Pozzato; S. Mishiro (Archives of Virology, 1996)

Mapping of transcriptional regulatory domains of pseudorabies virus immediate-early protein - S. Taharaguchi; H. Inoue; E. Ono; H. Kida; S. Yamada; Y. Shimizu (Archives of Virology, 1994)

Replication of rat coronavirus in a rat cell line, LBC - N. Hirano; K. Ono; Y. Sada; A. Inoue; T. Murakami; H. Takamaru (Archives of Virology, 1985)

Antigenic difference between intracellular and membrane antigens induced by herpesvirus of turkeys - M. Inoue; T. Mikami; H. Kodama; M. Onuma; H. Izawa (Archives of Virology, 1980)